Can single-use versus standard duodenoscope improve ergonomics in ERCP? A comparative, simulation-based pilot study - Cennamo, Vincenzo; Botter, Alberto; Landi, Stefano; Graziosi, Francesca; Bassi, Marco; Dabizzi, Emanuele; Ghersi, Stefania; Cerone, Giacinto; Bonfiglioli, Roberta (Endoscopy International Open, 2024)
Background and study aims Musculoskeletal disorders (MSDs) and injuries (MSIs) are frequent in gastrointestinal endoscopy. The aim of this study was to assess potential ergonomic advantages of a lighter single-use duodenoscope compared with a standard reusable one for endoscopists performing endoscopic retrograde cholangiopancreatography (ERCP).Methods Three experienced endoscopists performed an ergonomic, preclinical, comparative protocol-guided simulation study of a single-use and a standard reusable duodenoscope using an anatomic bench model. Surface EMG signals from left forearm and arm muscles were recorded. A commercial inertial sensor-based motion capture system was applied to record body posture as well.Results A significant lowering of root mean square amplitude and amplitude distribution of biceps brachii signal (ranging from 13% to 42%) was recorded in all the participants when using a single-use duodenoscope compared with a reusable one. An overall reduction of muscle activation amplitude and duration was also associated with the single-use duodenoscope for forearm muscles, with different behaviors among subjects. Participants spent most of the time in wrist extension (> 80%) and ulnar deviation (> 65%). A consistent pattern of functional range of motion employed for completing all procedures was observed.Conclusions Our study showed that a lighter scope has a promising effect in reducing upper arm muscle activity during ERCP with potential benefit on musculoskeletal health in the ERCP setting.
Keywords: ERC topics; Pancreatobiliary (ERCP/PTCD); Diagnostic ERC; Quality and logistical aspects; Quality management